Turkish immigrants in the mainstream of American life : theories of international migration - Ziyanak, Sebahattin; Sert, Bilal (Lexington Books, 2018)
This book explores the themes of citizenship in the migration of Turks to the United States. It discusses identity formation across generations among Turkish Americans and analyzes important differences between first and second generation Turkish Americans.